Chokri Küphida Kürao - Puzaso (Central Institute of Indian Languages Mysore, 1988)
This book is a primer for learning Chokri language.
Keywords: Chokri; Chokri Küphida Kürao; Bharatavani; Knowledge Through Indian Languages; Primer; Chokri